Change in the Mexican Technological Baccalaureate: The case of the Discipline of Science, Technology, Society and Values - Tinajero Villavicencio, Guadalupe; López Bonilla, Guadalupe; Pérez Fragoso, Carmen (Education Policy Analysis Archives, 2007)
This article reports partial results of a research project that attempts, among other things, to identify the scope of educational policies concerning structural reforms to the Mexican high school curriculum. In particular, it covers the curricular reform implemented during the 2004-2005 school year in vocational technological high schools, paying special attention to teacher's adoption of the new pedagogical proposal. The research was carried out in three technological high schools: Agricultural, Marine, and Industrial, where three teachers were observed while teaching a new discipline entitled: Science, Technology, Society and Values I. This is one out of three sequential subjects included in the new curriculum that substitute four subjects from the former historical–social sciences area. Our results showed a lack of teachers' appropriation of the pedagogical proposal introduced with the reform due, in part, to a lack of knowledge regarding its conceptual framework.